Insights into Meniscal Injuries Among Young Football Athletes: A Scoping Review - Riki Likardo; Hendri Neldi; Roma Irawan; Willadi Rasyid; Dally Rahman; Yovhandra Ockta; Firunika Intan Cahyani (Jurnal Penelitian Pendidikan IPA, 2023)
This comprehensive literature review delves into the prevalence, risk factors, management strategies, and outcomes related to meniscal injuries, particularly focusing on young football athletes. Drawing from eight scholarly articles, it covers various aspects of meniscal injuries, including incidence rates, treatment options, rehabilitation techniques, and long-term implications. Meniscal injuries are highlighted as significant in sports, notably in high-mobility activities like football, where sudden movements and twisting motions increase the likelihood of such injuries. The review explores common treatment methods such as meniscal repair, transplantation, and partial meniscectomy, along with tailored rehabilitation approaches aimed at facilitating athletes' return to play. Research indicates that while meniscal injuries are common among athletes, particularly in contact sports like football, early detection and proper treatment are crucial to mitigate lasting effects. Understanding knee joint anatomy and biomechanics is emphasized, along with the implementation of effective rehabilitation protocols to enhance joint stability and prevent re-injury. In summary, this literature review offers valuable insights into the multifaceted nature of meniscal injuries among young football athletes. By synthesizing evidence from diverse sources, it contributes to a deeper understanding of the epidemiology, management, and rehabilitation of meniscal injuries, informing clinical practices and guiding future research in sports medicine